History and Measurement of the Base and Derived Units - Treese, Steven A. (Springer International Publishing, 2018)
This book discusses how and why historical measurement units developed, and reviews useful methods for making conversions as well as situations in which dimensional analysis can be used. It starts from the history of length measurement, which is one of the oldest measures used by humans. It highlights the importance of area measurement, briefly discussing the methods for determining areas mathematically and by measurement. The book continues on to detail the development of measures for volume, mass, weight, time, temperature, angle, electrical units, amounts of substances, and light intensity. The seven SI/metric base units are highlighted, as well as a number of other units that have historically been used as base units. Providing a comprehensive reference for interconversion among the commonly measured quantities in the different measurement systems with engineering accuracy, it also examines the relationships among base units in fields such as mechanical/thermal, electromagnetic and physical flow rates and fluxes using diagrams. .